(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
After India gained its independence, the government set about the work of reorganizing thestates, and on November 1, 1956, Madhya Pradesh was officially recognized as the country’s mostpopulous state, given its name because of its central position. Because of the state’s geography andpopulation distribution, it was crucial to give the people involved the attention they deserved. From 1956to 2000, there were consistent shifts in the state’s average sex ratio, which, according to the 2001 census,was 920 females for every man. The situation with women’s literacy began to improve in the 1960s andcontinued to improve in the decades that followed. Women’s political consciousness and awarenessmanifested themselves in just specific contexts. Women’s participation remained dismally low. In thepast, women faced significant barriers to entering political office. The researcher set out to analyses theposition of women in Madhya Pradesh from the time of the state’s independence in 1956 till the year2000. In Madhya Pradesh, it was well understood that a woman’s social and economic mobility werestrongly impacted by her family’s status. Even while it was thought that there had been significant effortsto better women’s lot via education and socio-legal enactments, development in other areas, such aseconomic empowerment and political awareness and engagement, had lagged behind.